A Preliminary Study on Change of Serum Immunoglobulin G Glycosylation in Patients With Migraine - Xu, Jingwei; Wang, Yuan; Han, Yating; Liu, Ningfeng; Liu, Zhenming; Guo, Huailian; Zou, Xiajuan; Zhang, Jun (Frontiers in Neurology, 2022)
Background and Objectives Migraine is a common neurological disease, but its pathogenesis is still unclear. Previous studies suggested that migraine was related to immunoglobulin G (IgG). We intended to analyze the immune characteristics of migraine from the perspective of IgG glycosylation, and provide theoretical assistance for exploring its pathogenesis. Methods The differences in the serum level of IgG glycosylation and glycopeptides between the episodic migraine patients and healthy controls were analyzed by applying the poly (glycerol methacrylate) @ chitosan (PGMA@CS) nanomaterial in combination with matrix-assisted laser desorption/ionization-time of flight mass spectrometry (MALDI-TOF-MS). We constructed a binary classification model with Feedforward Neural Network using PyTorch 1.6.0 in Python 3.8.3 to classify the episodic migraine and healthy control group. Results Twenty migraine patients and 20 healthy controls were enrolled and the blood samples and clinical information were collected. Forty-nine IgG N-glycopeptides were detected in the serum of the subjects. The serum level of N-glycopeptide IgG1 G0-NF (p=0.012) was increased in migraine patients. The serum level of N-glycopeptide IgG3/4 G2FS (p=0.041) was decreased in migraine patients with family history of headache. It was found that the serum level of the IgG1 G1 (p=0.004) and IgG2 G0 (p=0.045) was increased in migraine patients with aura, while IgG2 G0N (p=0.043) in migraine patients with aura was significantly lower than that in migraine patients without aura. In addition, a linear Feedforward Neural Network (FFNN) was used to construct a binary classification model by detected IgG N-glycopeptides. The AUC value of the binary classification model which was constructed with 7 IgG N-glycopeptides was 0.857, suggesting a good prediction performance. Among these IgG N-glycopeptides that were constructed the model, IgG1 G0-NF was overlapped with the differential IgG N-glycopeptide between the migraine patients and healthy controls detected with MALDI-TOF-MS. Conclusion Our results indicated that the serum level of N-glycopeptides IgG1 G0-NF might be one of the important biomarkers for the diagnosis of migraine. To the best of our knowledge, this is the first study about the changes of IgG N-glycosylation in migraine patients by the method of MALDI-TOF-MS. The results indicated a relationship between the migraine and immune response.